Predictors of tennis performance of junior players - Mosoi, A. A.; Rascanu, R.; Gugu Gramatopol, C. (Procedia - Social and Behavioral Sciences, 2014)
The objective of our study was to identify the psycho-motor factors, their strength influencing the position of players in the national rank. We assume that athletes who achieve good scores in testing psycho-motor factors are likewise highly ranked. The study was conducted on 67 athletes, aged between 13 and 18 years. To evaluate these predictors, the participants were subjected to the Concentrated Attention Test, regarding the Motivation - The Sport Motivation Scale SMS - for coordination assessment - the Tapping and Tracing test and to measure personality the Revised NEO Personality-Inventory. Our survey identified one predictor on mental level (duration attention), one factor on motor-coordination level (tracing left hand) and one predictor on personality level (wish to succeed). In conclusion, players that featured highly developed psycho-motor skills also occupied a high position in the national rank.